Cultivating Emotional Intelligence among Indian Medical Students: Perceptions and Experiences - Rutam B Vaishnav; Darshankumar Dharaiya; Alvis Keisham; Anusha Prabhakaran; Jagdish Varma (JOURNAL OF CLINICAL AND DIAGNOSTIC RESEARCH, 2026)
Introduction: Emotional Intelligence (EI) is a critical attribute for medical professionals, encompassing self-awareness, selfregulation, motivation, empathy, and social skills. Indian medical students face exceptional stress due to intense academic competition, hierarchical structures, and limited mental health resources. Although structured EI interventions have demonstrated promise internationally in reducing burnout and improving clinical performance, systematic EI training remains largely absent from Indian medical curricula. Aim: To explore the perceptions and experiences of Indian medical graduates regarding the application of EI skills in their clinical and academic lives after completing a structured Value Added Course (VAC). Materials and Methods: This qualitative study was conducted at the Department of Psychiatry, Pramukhswami Medical College, Karamsad, affiliated with Shree Krishna Hospital, a tertiary care Institute in Gujarat, India, between September 2024 and April 2025. The study involved medical students who had participated in a three-month VAC titled “Developing Emotional Competencies,” based on Goleman’s EI model. The course addressed self-awareness, self-management, social awareness, and relationship management through interactive learning and reflective activities. The primary inclusion criterion was participation in the VAC on EI. A total of 10 students were eligible, of whom five students participated in the Group Interview (GI). The interview, conducted approximately one year after course completion, was audio-recorded and transcribed. Thematic analysis was performed following Braun and Clarke’s framework to identify patterns across the data. Results: Seven overarching themes emerged: EI in clinical practice, self-awareness management, social awareness and relationships, professional development, stress and burnout management, EI educational programs, and personal benefits. Students demonstrated concrete applications of EI in patient interactions, emphasising empathetic care while maintaining professional boundaries. Self-awareness emerged as foundational to all EI domains. Participants reported enhanced confidence in navigating emotionally charged interactions, improved recognition and management of stress, and normalised emotional experiences. Cross-cutting patterns revealed an evolution from theoretical understanding to practical application. Conclusion: Medical students perceive structured EI training as beneficial for fostering emotional awareness, interpersonal sensitivity, and adaptive coping during medical education. Embedding EI within medical curricula may offer a meaningful avenue to support the holistic development and emotional wellbeing of future healthcare professionals.